2017
DOI: 10.1111/ggi.13016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multifactorial intervention comprising resistance exercise, nutritional and psychosocial programs on frailty and functional health in community‐dwelling older adults: A randomized, controlled, cross‐over trial

Abstract: This 3-month multifactorial intervention reduced frailty and improved functional health. These intervention effects persisted for at least 3 months post-intervention. Geriatr Gerontol Int 2017; 17: 2034-2045.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
159
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(166 citation statements)
references
References 26 publications
6
159
1
Order By: Relevance
“…Initiatives such as group activities, goal setting, and checklists may also help improve nutritional status by encouraging consumption of a properly balanced diet. [35,74] Three studies included CGA or CGA-like strategies as an intervention,[36, 75,76] incorporating tools such as preventive home visits, multi-professional group meetings to discuss patients' care, and treatments being prescribed based on individual need. Our meta-analysis suggests that this tailored approach is successful in reducing frailty prevalence but it is difficult to ascertain whether a specific component was responsible for improvement, or if there was a combinatorial effect, due to the varied needs of the individuals taking part in those studies.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Initiatives such as group activities, goal setting, and checklists may also help improve nutritional status by encouraging consumption of a properly balanced diet. [35,74] Three studies included CGA or CGA-like strategies as an intervention,[36, 75,76] incorporating tools such as preventive home visits, multi-professional group meetings to discuss patients' care, and treatments being prescribed based on individual need. Our meta-analysis suggests that this tailored approach is successful in reducing frailty prevalence but it is difficult to ascertain whether a specific component was responsible for improvement, or if there was a combinatorial effect, due to the varied needs of the individuals taking part in those studies.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…When frailty is suspected, the underlying disease should be identified and managed in a clinical setting, and a multifactorial intervention comprising resistance exercise, protein-rich food intake and a psychosocial program should be used to improve frailty. 30 In conclusion, the present prospective study of Japanese older adults shows that the risks of death and disability in individuals with mild diabetes are strongly affected by the presence of frailty. The risks of all-cause mortality and incident disability among frail adults with diabetes were 5.0-and 3.9-fold, respectively, those of non-frail adults without diabetes.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, the present study has practical implications for frailty assessment of older adults at community‐based health checkups, regardless of diabetes status. When frailty is suspected, the underlying disease should be identified and managed in a clinical setting, and a multifactorial intervention comprising resistance exercise, protein‐rich food intake and a psychosocial program should be used to improve frailty …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that exercise improves memory function in mice, including AD model mice, by triggering hippocampal neurogenesis and increasing brain‐derived neurotrophic factor expression . In addition, physical activity reduces the risk of cardiovascular disease, and prefrail or frail older adults can reduce frailty by performing interventions combining resistance exercise, nutritional education, and psychosocial programs . This is also expected to improve cognitive function, advance physical function, and promote health through physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, physical activity reduces the risk of cardiovascular disease, 16 and prefrail or frail older adults can reduce frailty by performing interventions combining resistance exercise, nutritional education, and psychosocial programs. 17 This is also expected to improve cognitive function, advance physical function, and promote health through physical activity. However, it is also important to select subjects who will benefit the most from these activities.…”
Section: By Comparing Changes In Tdas Scores and Physical Function Tementioning
confidence: 99%